International snapshot of new psychoactive substance use: Case study of eight countries over the 2019/2020 new year period. (1st April 2021) - Bade, Richard; White, Jason M.; Chen, Jingjing; Baz-Lomba, Jose Antonio; Been, Frederic; Bijlsma, Lubertus; Burgard, Daniel A.; Castiglioni, Sara; Salgueiro-Gonzalez, Noelia; Celma, Alberto; Chappell, Andrew; Emke, Erik; et al.
Highlights: Treatment plants in eight countries participated in a wastewater-based study NPS were monitored for up to 15 days over the New Year period 16 Substances were found, with methcathinone and N-ethylpentylone most common Eutylone was a new generation cathinone found in Oceania, Europe and the USA Abstract: There is considerable concern around the use of new psychoactive substances (NPS), but still little is known about how much they are really consumed. Analysis by forensics laboratories of seized drugs and post-mortem samples as well as hospital emergency rooms are the first line of identifying both 'new' NPS and those that are most dangerous to the community. However, NPS are not necessarily all seized by law enforcement agencies and only substances that contribute to fatalities or serious afflictions are recorded in post-mortem and emergency room samples. To gain a better insight into which NPS are most prevalent within a community, complementary data sources are required. In this work, influent wastewater was analysed from 14 sites in eight countries for a variety of NPS. All samples were collected over the 2019/2020 New Year period, a time which is characterized by celebrations and parties and therefore a time when more NPS may be consumed. Samples were extracted in the country of origin following a validated protocol and shipped to Australia for final analysis using two different mass spectrometric strategies. In total, more than 200 were monitored of which 16 substances were found, with geographical differences seen. This case study is the most comprehensive wastewater analysis study ever carried out for the identification of NPS and provides a starting point for future, ongoing monitoring of these substances. Graphical abstract: Image, graphical abstract